2020
DOI: 10.1002/mnfr.201901329
|View full text |Cite
|
Sign up to set email alerts
|

Improved Glucose Intolerance through a Distinct Mouse Olfactory Receptor 23‐Induced Signaling Pathway Mediating Glucose Uptake in Myotubes and Adipocytes

Abstract: Scope: It is aimed to determine the role of mouse olfactory receptor 23 (MOR23) in regulation of glucose uptake in myotubes and adipocytes and investigate whether administration of a possible MOR23 ligand,-cedrene, attenuates the high fat diet (HFD)-induced glucose intolerance by enhancing the OR-mediated signaling pathway in mice. Methods and Results: MOR23 is genetically inactivated by specific small interfering RNA in C2C12 myotubes and 3T3-L1 adipocytes and stimulated with-cedrene under both basal and insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition, some components (piperonal and filbertone) targeting adipose cAMP signaling that have great potential to maintain glucose homeostasis are also introduced in this part. α-Cedrene, a member of the class of organic compounds known as cedrane and iso-cedrane sesquiterpenoids, stimulates glucose uptake by stimulated the GLUT4 translocation to the cytomembrane in the C2C12 myotubes and 3T3-L1 adipocytes via mouse olfactory receptor 23/cAMP/PKA pathway [89]. Pachymic acid, one of the major chemical components of Poria cocos, stimulates glucose uptake via increasing the expression of GLUT4 and enhancing the redistribution of GLUT4 from intracellular vesicles to the plasma membrane of 3T3-L1 adipocytes.…”
Section: The Dietary Bioactive Ingredients Targeting Adipose Tissue Camp Signaling For Glucose Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some components (piperonal and filbertone) targeting adipose cAMP signaling that have great potential to maintain glucose homeostasis are also introduced in this part. α-Cedrene, a member of the class of organic compounds known as cedrane and iso-cedrane sesquiterpenoids, stimulates glucose uptake by stimulated the GLUT4 translocation to the cytomembrane in the C2C12 myotubes and 3T3-L1 adipocytes via mouse olfactory receptor 23/cAMP/PKA pathway [89]. Pachymic acid, one of the major chemical components of Poria cocos, stimulates glucose uptake via increasing the expression of GLUT4 and enhancing the redistribution of GLUT4 from intracellular vesicles to the plasma membrane of 3T3-L1 adipocytes.…”
Section: The Dietary Bioactive Ingredients Targeting Adipose Tissue Camp Signaling For Glucose Homeostasismentioning
confidence: 99%
“…This progress is through inhibiting the activity of PDE and increasing the level of intracellular cAMP in L6 myocytes and KK-Ay mice [ 87 , 88 ]. Similarly, α-cedrene, the ligand of mouse olfactory receptor 23, stimulates glucose uptake by stimulating the GLUT4 translocation to the cell membrane in the C2C12 myotubes via mouse olfactory receptor 23/cAMP/PKA signaling pathway [ 89 ]. In vivo, Samad et al reported that [6]-gingerol, a major component of zingiber officinale, improves hyperglycemia by stimulating GLUT4 transporters translocation to cytomembrane in skeletal muscle [ 45 ].…”
Section: Skeletal Musclementioning
confidence: 99%
“…Gain-of-function mutation of Adcy3, a downstream signal-transducing molecule in the canonical olfactory signaling machinery, leads to lower body weights and fat mass in mice fed HFD [ 50 ]. Similarly, we later demonstrated that haploinsufficiency of Adcy3 leads to obesity in the absence of hyperphagia in mice fed either HFD or chow [ 51 ].…”
Section: Biological Functions Of Ectopic Ors Responding To Odorant Compounds In the Non-chemosensory Tissuesmentioning
confidence: 99%
“…A sesquiterpene α-cedrene [134] from cedarwood oil significantly increased the translocation of GLUT4 and increased glucose uptake in human hepatocytes in vitro, and improved glucose intolerance induced by a high-fat diet in vivo through the activation of the murine olfactory receptor Olfr16 [135]. A similar effect of α-cedrene in mice with IR was ascribed to the interaction of α-cedrene with the murine olfactory receptor 23 (Mor23) [136]. These reports suggest the possible involvement of odorant receptors in the control of IR.…”
Section: Terpenesmentioning
confidence: 99%